Considerations on method, order and understanding in René Descartes and Benedictus de Spinoza - da Rocha Fragoso, Emanuel Angelo (Estudios de Filosofía, 2006)
The ordine geometrica is a splitting up of definitions and axioms that are self evident. The parallelism between both orders in Spinoza’s System, the order cognoscendi and the order essendi, enables one to postulate the total intensity of the Real, which necessarily implies a likeness between the finite understanding, inasmuch as it is a producer of the former order, and the infinite understanding, inasmuch as it is a producer of the latter order, which is absent in Cartesian Philosophy. Mortral Gueroult, considers Descartes’ Method as a geometrical one because it strictly obeys the rule that ensures all rigour in Geometry; while Spinoza’s is so because, like Gemoetry, he constructs the concepts from the objects.